Surgical and Bronchoscopic Lung Volume Reduction in Chronic Obstructive Pulmonary Disease. (29th December 2014) - Meena, Manoj; Dixit, Ramakant; Singh, Mrityunjaya; Samaria, Jai Kumar; Kumar, Surendra
Abstract : Chronic obstructive pulmonary disease (COPD) is the most extensively studied and researched disease in pulmonology and a cause of significant morbidity, mortality, and financial burden on patient's family and country's economy. Its management continues to be a challenge to both the physician and the patient's family. So far, it is preventable and treatable but not curable. Emphysema, a phenotype of COPD, is the most debilitating condition associated with progressive exercise intolerance and severe dyspnea. Despite decades of research, medical treatments available so far have helped improve quality of life and slowed down the decline in respiratory function but did not significantly improve the survival benefits. Though surgical lung volume reduction (LVR) procedures have shown some promise in context to functional gains and survival but, only in a carefully selected group of patients, bronchoscopic LVR procedures are yet to explore their full potential and limitations. This paper retrospectively studied the developments so far, medical and surgical, with special emphasis on the bronchoscopic procedures of lung volume reduction, and tried to comparatively analyze the risks and benefits of each one of them through various trials and studies done to date.